Punching above their weight: a network to understand broader determinants of increasing life expectancy - Fran Baum; Jennie Popay; Toni Delany-Crowe; Toby Freeman; Connie Musolino; Carlos Alvarez-Dardet; Vinya Ariyaratne; Kedar Baral; Paulin Basinga; Mary Bassett; David M. Bishai; Mickey Chopra; et al. (BMC, 2018)
Abstract Background Life expectancy initially improves rapidly with economic development but then tails off. Yet, at any level of economic development, some countries do better, and some worse, than expected - they either punch above or below their weight. Why this is the case has been previously researched but no full explanation of the complexity of this phenomenon is available. New research network In order to advance understanding, the newly formed Punching Above Their Weight Research Network has developed a model to frame future research. It provides for consideration of the following influences within a country: political and institutional context and history; economic and social policies; scope for democratic participation; extent of health promoting policies affecting socio-economic inequities; gender roles and power dynamics; the extent of civil society activity and disease burdens. Conclusion Further research using this framework has considerable potential to advance effective policies to advance health and equity.